The Prevention of Spontaneous Combustion in the North Western Area - S. Vardy (The Institute of Materials, Minerals and Mining, 1905)
The paper notes that the extraction of 22% of the remaining workable reserves in the north western area involves a risk of spontaneous combustion higher than is normal in Britain. Mining systems have been tailor made in order to minimize the risk of spontaneous heatings, and these systems are described. Well-proved methods of combating spontaneous combustion are referred to, as well as the limitations which now apply to them as the result of the introduction of modern mining techniques. A substantial part of the paper is devoted to the circumstances in which spontaneous combustion occurs underground in the north western area. Several actual incidents which have occurred in the last few years, along with the practical application of the lessons learned, are described. Of particular note are: a) the procedure adopted in the north western area to equalize pressure differences across stoppings using pressure chambers, and b) a retreat mining system, primarily designed to deal with high methane emission and steep gradients, which also affords some protection against spontaneous combustion.